Akulturasi dan asimilasi budaya di nusantara - Faqih, Agus; Ghozi, Ahmad; Afrizal, Yusril; Amani, Hanan Mahira (Maliki Interdisciplinary Journal, 2024)
This article discusses the process of acculturation and assimilation of Islamic culture in the archipelago, which occurred through peaceful interactions between traders, scholars and religious propagators with local communities. Various aspects of human life were influenced by the arrival of Islam, including language, art, customs and social structure. As a result, a remarkable synergy between Islamic culture and local culture was formed. Local cultural identity was influenced by the confluence of Indian, Chinese, Arab, Persian and European cultures in the archipelago. Factors such as location, economics, politics, social, religious, technology and education influenced this process, all of which affected the interaction of Indonesian cultures. Education, spiritual enrichment, increased tolerance and changes in political structure were all outcomes. Maintaining a balance between outside and local influences and managing ethnic diversity remains a challenge. This phenomenon demonstrates the ability of Indonesians to maintain their original identity while absorbing new elements, resulting in a dynamic and harmonious cultural diversity.